PENGARUH INTEGRITAS, PROFESIONALISME, DAN BEBAN KERJA AUDITOR TERHADAP KUALITAS AUDIT - Gumulya Sonny Marcel Kusuma (JURNAL KOMPETITIF, 2021)
This study examines the influence of integrity, professionalism, workload of auditors on the audit quality. This research uses convenience sampling technique to select the respondent. Data were collected through a survey on 46 respondents auditors of the Public Accountant of Palembang. Structural Equation Model (SEM) with Partial Least Square (PLS) was applied to analyzed the data.The result of this research indicate positive influence of integrity on audit quality, indicate negative influence of workload on audit quality. Futhermore, it was found that there were no significant influence professionalism on the audit quality.